Identidade e ficcionalização no espaço biográfico em Dois Irmãos, de Milton Hatoum - Santos, Adriana de Oliveira Francisco (2014)
This essay proposes to analyze the novel DoisIrmãos, by Milton Hatoum. It aims to reflect on the relationship between the socio-cultural-economic context and its influence on the identity of the characters, as well as highlight the memory space as an agent that reframes the past in the present. To achieve these goals, the following question was risen: How does the notion of subject, constructed in relation to the other, forms itself against the multiple voices echo in the identity formation process of the characters? The hypotheses in the literary text, especially in the novel taken as the object of this work, the resulting changes in processing of manauara society affects the way that the narrator looks to the focused objects and, therefore, are essential for understanding identity forming elements. We also believe that from memory the narrator-protagonist entwines the past and the present, creating images woven around the tension between remembering and forgetting, as well as between collective memory and personal memory. The theoretical foundations about identity formation relies mainly on studies of Stuart Hall (2004) and Zygmund Bauman (2001, 2005). Regarding memory, we are referring to the theories of Bosi (2009); Ricoeur (2007) and Bergson (2006). Among the final considerations, the following stand out: the distressing search for Nael, narrator-character, that, to recover his past and, consequently, their identity, gains truth through the imaginary and the socio-cultural-economic context; the effect of this demand is the mobility of the narrator between otherness and biographical fragments assembled in the biographic space